Aggravation of exercise-induced intestinal injury by Ibuprofen in athletes - Van Wijck, K.; Lenaerts, K.; van Bijnen, A. A.; Boonen, B.; van Loon, L. J. C.; Dejong, C. H. C.; Buurman, W. (Medicine & Science in Sports & Exercise, 2012)
Introduction: Nonsteroidal anti-inflammatory drugs are commonly used by athletes to prevent anticipated exercise-induced pain, thereby putatively improving physical performance. However, these drugs may have potentially hazardous effects on the gastrointestinal (GI) mucosa during strenuous physical exercise. The aim of the current study was to determine the effect of oral ibuprofen administration before exercise on GI integrity and barrier function in healthy individuals.